2022
DOI: 10.3389/fendo.2022.987488
|View full text |Cite
|
Sign up to set email alerts
|

Association between lncRNAs in plasma exosomes and diabetic retinopathy

Abstract: BackgroundLong noncoding RNA (lncRNA) in plasma exosomes is a potential non-invasive diagnostic biomarker for diabetic retinopathy (DR). However, the changes in plasma exosomal lncRNAs and diagnostic relevance in patients with DR patients remain unclear.MethodsA case–control study with type 2 diabetes mellitus (T2DM) and patients with comorbid DR were enrolled, and their clinical information and blood samples were collected. Plasma exosomes were extracted, and the relative expression levels of representative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Another study analyzed lncRNAs in plasma EVs from individuals with T2DM and comorbid DR and identified lncRNA DLX6-AS1, PRINS, and FAM190A-3 as potential predictor of DR, with separate AUC values of 0.658, 0.798, and 0.603. Notably, the combination of DLX6-AS1 and PRINS obtained an AUC of 0.813, which even reached 0.860 in males 93 .The construction of an EV-related ceRNA network in DR has revealed a series of aberrant expressed lncRNAs, miRNAs, and mRNAs 94 , highlighting the broad prospects of vesicular RNAs in diagnosis applications.…”
Section: Evs In Dr Pathology and Diagnosismentioning
confidence: 99%
“…Another study analyzed lncRNAs in plasma EVs from individuals with T2DM and comorbid DR and identified lncRNA DLX6-AS1, PRINS, and FAM190A-3 as potential predictor of DR, with separate AUC values of 0.658, 0.798, and 0.603. Notably, the combination of DLX6-AS1 and PRINS obtained an AUC of 0.813, which even reached 0.860 in males 93 .The construction of an EV-related ceRNA network in DR has revealed a series of aberrant expressed lncRNAs, miRNAs, and mRNAs 94 , highlighting the broad prospects of vesicular RNAs in diagnosis applications.…”
Section: Evs In Dr Pathology and Diagnosismentioning
confidence: 99%
“…The combination of exosomal DLX6-AS1 and PRINS has good diagnostic value for diabetic retinopathy (DR), particularly in males. Exosomal PRINS expression may be a predictive and diagnostic biomarker for DR in females [ 59 ].…”
Section: Clinical Applications Of Exosomes In T2dm Managementmentioning
confidence: 99%
“…The expression of exosome lncRNA PRINS is also involved in the prediction and diagnosis of female DR as a unique biomarker. 147 In an atrial fibrillation (AF) diagnosis study, the authors analyzed the serum exosome lncRNAs of AF patients and the normal population and discovered that lncRNA LOC107986997 in serum exosomes was closely correlated with AF expression, potentially making it a sensitive and specific diagnostic biomarker for AF. 148 Furthermore, lncRNA-Linc00662, lncRNA-CHASERR, and lncRNA-PCA3 were significantly elevated in the extracellular vesicles isolated from the urine of prostate cancer (PC) patients.…”
Section: Evs As Disease Marker In Diagnostic Applicationmentioning
confidence: 99%